2012
DOI: 10.1038/sc.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Muscle perfusion of posterior trunk and lower-limb muscles at rest and during upper-limb exercise in spinal cord-injured and able-bodied individuals

Abstract: Study design: Nonrandomized-controlled trial. Objectives: To assess muscle perfusion at rest and during arm-cranking exercise (ACE) in upper and lower posterior trunk and vastus lateralis (VL) muscles in individuals with spinal cord injury (SCI) and controls (C). Setting: Exercise Physiology-Biochemistry Laboratory. Methods: Eight SCI with thoracic lesion and eight C received injections of radioactive tracer to trapezius (TRAP), latissimus dorsi (LAT) and VL. Radioactive counts were recorded with a g-camera fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Demiot et al [13] revealed a significant reduction in resting cutaneous microcirculation, measured by means of laser Doppler, after 56 days of bed rest in sedentary individuals. Furthermore, Zafeiridis et al [28] measured resting muscle perfusion and capillary flow in vastus lateralis muscle of spinal cord-injured and able-bodied individuals by means of local clearance of a radioactive tracer ( 99m Tc-pertechnetate). Results showed that microcirculation in paralyzed subjects was reduced by~40% compared with that in able-bodied subjects [28].…”
Section: Evidence That Chronic Physical Constraint Affects Circulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Demiot et al [13] revealed a significant reduction in resting cutaneous microcirculation, measured by means of laser Doppler, after 56 days of bed rest in sedentary individuals. Furthermore, Zafeiridis et al [28] measured resting muscle perfusion and capillary flow in vastus lateralis muscle of spinal cord-injured and able-bodied individuals by means of local clearance of a radioactive tracer ( 99m Tc-pertechnetate). Results showed that microcirculation in paralyzed subjects was reduced by~40% compared with that in able-bodied subjects [28].…”
Section: Evidence That Chronic Physical Constraint Affects Circulatiomentioning
confidence: 99%
“…Furthermore, Zafeiridis et al [28] measured resting muscle perfusion and capillary flow in vastus lateralis muscle of spinal cord-injured and able-bodied individuals by means of local clearance of a radioactive tracer ( 99m Tc-pertechnetate). Results showed that microcirculation in paralyzed subjects was reduced by~40% compared with that in able-bodied subjects [28]. Again, although the methods and the subjects included in the previous studies are different from ours, the results are in line with our findings.…”
Section: Evidence That Chronic Physical Constraint Affects Circulatiomentioning
confidence: 99%
“…; Zafeiridis et al . ), an important mechanism to promote positive endothelial adaptations to exercise, but there is still insufficient evidence for exercise intervention to result in improved cutaneous perfusion through augmented endothelial function. Lifestyle modifications have been found to improve local vasodilatory responses to insulin iontophoresis among individuals with the metabolic syndrome (Vinet et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that beneficial adaptations to training conditions can lead to improvements in sublesional macrovascular endothelial function, whether or not increases in lean tissue mass occur in parallel (Olive et al 2003;de Groot et al 2005;Thijssen et al 2005;Totosy de Zepetnek et al 2015b). Likewise, there is evidence for improved cutaneous and muscle microvascular perfusion responses to acute bouts of exercise in persons SCI (Muraki et al 1995(Muraki et al , 1996Theisen et al 2001;Van Duijnhoven et al 2009;Zafeiridis et al 2012), an important mechanism to promote positive endothelial adaptations to exercise, but there is still insufficient evidence for exercise intervention to result in improved cutaneous perfusion through augmented endothelial function. Lifestyle modifications have been found to improve local vasodilatory responses to insulin iontophoresis among individuals with the metabolic syndrome (Vinet et al 2015), but the same has yet to be demonstrated in persons with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…interleukins-6 and blood flow to the exercising muscles). 49,50 This study has some potential limitations. First, our findings are limited to individuals with complete thoracic lesions.…”
Section: Discussionmentioning
confidence: 99%